Ricketts' Cephalometric Analysis for Saudi Population - Ayesha Siddika; Shaifulizn Ab. Rahman; Mohammad Khursheed Alam (Association of Support to Oral Health Research (APESB), 2022)
Objective: To evaluate the cephalometric norm for Saudi sample by Ricketts analysis (RA). Material and Methods: In this cross-sectional study, cephalometric radiographs were taken for 500  samples. The subjects included 250 males and 250 females. The ages of the subjects ranged from 18-30years. The criteria of selection were based on Class I incisor relationship, no skeletal abnormality and no previous orthodontic treatment. Lateral cephalometric radiographs were taken, traced and digitized by SPSS software, according to RA. An independent t-test was used to test the level of significance between genders.  Results: Significant disparities found between Saudi males and females in dental and soft tissue measurements. The result showed that the distal position of the maxillary first molar to pterygoid vertical plane (U6 to Ptv) measurement was highly significantly greater (p<0.001) in Saudi males than females. Lower incisor to A- Pog (L1 to A-Pog) and lower lip to E plane was significantly longer (p<0.05) in Saudi males than females. Other measurements had no significant difference between Saudi males and females. Conclusion: The craniofacial morphology of the Saudi males was different from Saudi females using Ricketts analysis. This study will help the clinicians to diagnosis and treatment planning of orthodontic and orthognathic patients.